Transmission of Streptococcus dysgalactiae subsp. equisimilis between Child and Dog in an Aboriginal Australian Community. (10th June 2013) - Schrieber, L.; Towers, R.; Muscatello, G.; Speare, R.
Summary Streptococcus dysgalactiae subsp. equisimilis (SDSE), also known as group G and C streptococci, is becoming increasingly recognized as a pathogen in humans. We report here the finding of an identical strain of SDSE in the throat of a child and their dog in an Aboriginal Australian community. The strain was identified using the API 20Strep system, 16S rRNA gene sequencing, emm sequence typing (emmST) and multilocus sequence typing (MLST) as a group C SDSE, stC839.5 and ST‐3. Carriage of this strain by a human and dog in the same household justifies detailed epidemiological studies using molecular typing to clarify the extent of cross‐species transmission and sharing of SDSE and other group G and C streptococci, and its impact in these communities.